Addition of Fermented Green Tea Dregs and Probiotic Lactobacillus sp. in Cihateup Duck Ration on Chemical Quality of Meat - Kusmayadi, Andri; Sundari, Ristina Siti; Sumaryana, Yusuf (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Green tea is widely consumed by the people of Indonesia as a beverage or processed food. Green tea dregs contain antioxidant compounds that have many pharmacological properties. On the other hands, green tea dregs contain tannin which can reduce digestibility so that further processing needs to be done by fermenting so that the digestibility increases. Fermented green tea dregs combined with probiotic Lactobacillus sp. is thought to be able to have a more significant impact on the growth of livestock and their products. The aim of this study was to examine the effect of adding a combination of fermented green tea dregs (ATHF) and probiotic Lactobacillus sp. in the ration on the chemical quality of Cihateup duck meat. The study was conducted experimentally using 60 Cihateup ducks which were randomly grouped into 4 groups of feed treatment as follows: T1 (100% basal feed/0% ATHF), T2 (PB + 1% ATHF + 3% probiotics), T3 (PB + 2% ATHF + 2% Probiotic) and T4 (PB + 3% ATHF + 1% Probiotic). The parameters of this study were the chemical quality of Cihateup duck meat which consisted of water content, protein content and fat content. The results showed that the addition of a combination of ATHF and probiotic Lactobacillus sp. significant effect (P<0.05) on the protein content and fat content of meat, while the water content parameter has no significant effect (P>0.05). T2 treatment produced the highest meat protein content and T1 treatment resulted in lower meat fat content than other treatments.